PENERAPAN METODE RESITASI PADA PENGAJARAN FISIKA UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA DI KELAS VIIB PADA TAHUN PELAJARAN 2017/2018 - Rosdiana, Rosdiana; Herayanti, Lovy; Gummah, Syifaul (Jurnal Ilmiah IKIP Mataram, 2019)
This type of research is classroom action research. The implementation of this research is conducted in two cycles, each cycle consists of two 4-stage meetings, namely: (1) planning (planning); (2) implementation (action); (3) observation (observing); (4) analysis and reflinging (reflecting). Data collection method used is documentation, observation / observation of written test. Based on research results of application of recitation improve student achievement. From the results of evaluation of classical completeness learning outcomes in cycle I, the average value of students 70.61 with 63.63% classical completeness with a total number of students who completed 21 students and 12 unfinished students from 33 students. While in Cycle II obtained the average value of 85.45 students with a total number of students who complete as many as 29 students and unfinished 4 students from 33 students with classical thoroughness 87.87%, thus the percentage of student learning completeness meets the criteria set ie â‰¥85%. Thus proves that the application of rehabilitation method can improve student’s learning achievement.